THE RELATIONSHIP BETWEEN PARKINSON'S DISEASE AND SHORT-CHAIN FATTY ACIDS - Malika M. Raimova; Sayyora Z. Sodikova (Central Asian Journal of Medicine, 2025)
Over the past ten years, growing evidence from research has emphasized the potential impact of bacterial communities in the human gut microbiota and their metabolites on both health and disease. Research has demonstrated that disruptions in gut bacteria, known as dysbiosis, can lead to disease and changes in the production of bacterial metabolites, which in turn can disrupt the immune system and metabolism. Short-chain fatty acids (SCFAs), including butyrate, acetate, and propionate, are produced through bacterial fermentation in the gut. Changes in the gut microbiota's metabolites have been linked to the development of various neurological disorders, such as Alzheimer's disease, multiple sclerosis, Parkinson's disease, amyotrophic lateral sclerosis, as well as mental health conditions like stress, anxiety, depression, autism, vascular dementia, schizophrenia, stroke, and neuromyelitis optica spectrum disorders, among others. Deciphering the mechanisms of regulation of neuronal function using propionic, butyric and acetate acids will allow us to identify new pharmacological targets for the treatment of various diseases of the central nervous system.The purpose of this review is to prove that the intestinal microbiota and its metabolites as short—chain fatty acids are a separate functioning system of the body.